2012
DOI: 10.1093/carcin/bgs130
|View full text |Cite
|
Sign up to set email alerts
|

MiR-145 modulates multiple components of the insulin-like growth factor pathway in hepatocellular carcinoma

Abstract: Profiling of microRNA expression in human cancers has highlighted downregulation of miR-145 as a common event in epithelial malignancies. Here, we describe recurrent underexpression of miR-145 in hepatocellular carcinoma (HCC) and the identification of a biological pathway by which miR-145 exerts its functional effects in liver tumorigenesis. In a cohort of 80 HCC patients, quantitative reverse transcription polymerase chain reaction corroborated reduced miR-145 expression in 50% of tumors, which also correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 37 publications
6
51
0
Order By: Relevance
“…A number of recent studies have focused on the role of miR-145 in multiple cellular pathways underlying carcinogenesis. For example, miR-145 has been found to inhibit cancer cell growth, invasion, and metastasis by suppressing EGFR and NUDT1 in lung adenocarcinoma, FSCN-1 in esophageal squamous cell carcinoma, N-cadherin in gastric carcinoma, and IGF in hepatocellular carcinoma [38][39][40][41]. In our experiments, miR-145 expression in the urothelial carcinoma cell lines T24 and KU7 induces cell senescence without apoptosis.…”
Section: Discussionsupporting
confidence: 48%
“…A number of recent studies have focused on the role of miR-145 in multiple cellular pathways underlying carcinogenesis. For example, miR-145 has been found to inhibit cancer cell growth, invasion, and metastasis by suppressing EGFR and NUDT1 in lung adenocarcinoma, FSCN-1 in esophageal squamous cell carcinoma, N-cadherin in gastric carcinoma, and IGF in hepatocellular carcinoma [38][39][40][41]. In our experiments, miR-145 expression in the urothelial carcinoma cell lines T24 and KU7 induces cell senescence without apoptosis.…”
Section: Discussionsupporting
confidence: 48%
“…20,21 Insulin-like growth factor I receptor activates multiple downstream signaling cascades, including PI3K/AKT and MAPK/ERK signaling pathways, which regulate cell proliferation, differentiation, and survival. [22][23][24][25][26][27] Recent studies have identified some miRNAs posttranscriptionally regulating IGFIR, such as miR-145, miR-375, and miR-143, suggesting that miRNAs targeting IGFIR have an important role in carcinogenesis. 28,29 In this study, we confirmed that overexpression of miR-100 in osteosarcoma cells inhibited cell proliferation, migration, invasion, and decreased the levels of p-AKT and p-ERK1/2, HIF-1a, and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that miR-145 is important in mediating placental growth in humans (Farrokhnia et al, 2014;Forbes et al, 2012). One of the targets of miR-145 is the type-1 insulin-like growth factor receptor (IGF1R) (La Rocca et al, 2009;Law et al, 2012) and IGF1R mRNA has been previously shown to be present in endometrium (Zhou et al, 1994). Despite this, to our knowledge, its role in regulating human endometrial receptivity or implantation remains to be explored.…”
Section: Introductionmentioning
confidence: 99%